2018
DOI: 10.29252/johe.7.4.209
|View full text |Cite
|
Sign up to set email alerts
|

Making a more comprehensive Persian version of the Impact on Participation and Autonomy (IPA-p) scale; The Perspectives of Experts and MS patients

Abstract: Article InfoBackground: After all efforts made to introduce a valid and reliable tool for measuring the health of patients, such as MS sufferers, the concept of "participation and autonomy", which might be affected by the disease, has been introduced. An efficient health measurement should consider all different aspects of a patient's life. This research was conducted aimed at introducing a new aspect of the individual's life that seems necessary to be added to the health measurement scale of Persian-speaking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The fifth part is about autonomy in obtaining academic qualifications which includes 3 questions. The sixth part is about autonomy in the acquisition and preservation of a job and consists of seven questions; finally, there were 5 questions related to being active in religious affairs, which were added to the English version of IPA (IPA-e), based on the results obtained from a previous work on (13). The validity and reliability of the questionnaire was obtained in a similar study, where about 50% of public respondents reported their perception of their participation to be "good" or "very good," and 60 percent of the experts reported the ability of the IPA-p scale to be desirable and excellent.…”
Section: Methodsmentioning
confidence: 99%
“…The fifth part is about autonomy in obtaining academic qualifications which includes 3 questions. The sixth part is about autonomy in the acquisition and preservation of a job and consists of seven questions; finally, there were 5 questions related to being active in religious affairs, which were added to the English version of IPA (IPA-e), based on the results obtained from a previous work on (13). The validity and reliability of the questionnaire was obtained in a similar study, where about 50% of public respondents reported their perception of their participation to be "good" or "very good," and 60 percent of the experts reported the ability of the IPA-p scale to be desirable and excellent.…”
Section: Methodsmentioning
confidence: 99%